Service delivery system and customer patronization : a comparison of ethnic restaurants in Shah Alam / Zulhan Othman - Othman, Zulhan (2007)
In today's sophisticated environment demand by restaurant customers for the highest levels of efficiency, quality, flexibility and dependability in the service delivery system has increased tremendously. Many restaurant businesses recognize that attaining customer satisfaction through efficient service delivery is a key to their business survival and they are well aware that having a loyal base of satisfied customers increases sales, reduces costs and builds market shares. This study examines to what extent the service delivery system influences customers' patronization. It also examines the customers' perceptions, through their dining experiences, of the service delivery systems in two types of ethnic restaurants (Mamak and Malay restaurants) in the city of Shah Alam, as well as their intention of re-patronization. Sample populations for this study were from restaurant customers who had experienced dining at Malay and Mamak restaurants. Respondents were randomly chosen at three popular supermarkets in Shah Alam city, Giant, Tesco and Macro and three shopping complexes, SACC Mall, Plaza Alam Central Mall and PKNS complex. Through personally administered questionnaires a significant amount of data was gathered. A series of analyses looking at frequencies, mean scores, standard deviation through descriptive and parametric statistics was undertaken. Overall, some useful insights or predictors were obtained. Results revealed that as well as food elements (taste, variety and quality of food), service attributes such as efficient and fast service were also found to be important in influencing customers to dine. In fact, other service delivery components such as operating environment (concept, layout, pleasant ambience and conducive dining environments, hygiene and cleanliness as well as entertainment) and human elements (friends and word of mouth) also moderate their patronization. In comparing customer views of the service delivery system (food, service, operating and human) and intention of re- patronization in Malay and Mamak restaurants some significant differences appeared in respondents' evaluation. Respondents professed that Malay restaurants offered more variety and versatility and displayed better presentation of food compared to Mamak restaurants: Nevertheless, their view changed with regard to service and other dimensions. Respondents strongly agreed that the majority of Mamak restaurants offered slightly better services and provided more conducive operating elements and this influenced their intention to repeat patronization. In addition, social influences also slightly moderated their intention to go to a particular restaurant. In this case again, Mamak restaurants were preferred by most of the respondents compared to Malay restaurants. The different perceptions especially among the restaurant customers of service and operating environment attributes have provided significant impact and implications especially for Malay restaurant operators. Malay restaurants are perhaps least able to attract more customers at all periods and consequently this probably will lead to an inability to increase their business prosperity as opposed to Mamak restaurants. This scenario highlights several important points, which should be acted on by most of the Malay restaurants operators to better understand customer needs. Then they can be well positioned to take advantage of the growing trends in eating habits of customers in Malaysia.